CORRELATION BETWEEN FASTING BLOOD GLUCOSE LEVELS AND SERUM TRIGLYCERIDE AND HDL CHOLESTEROL LEVELS IN ELDERLY PATIENTS WITH TYPE 2 DIABETES MELLITUS - Dwi Retnoningrum; Salma Tyas Salsabila; Banundari Rachmawati; Nyoman Suci Widyastiti (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Blood glucose levels over normal limits are a hallmark of diabetes mellitus (DM), a chronic metabolic disease with several causes. Disorders in lipid metabolism can result from type 2 diabetes mellitus. This study investigated the correlation between fasting blood glucose (FBG) levels and serum triglyceride and HDL cholesterol in elderly people with type 2 diabetes. Objectives: To prove that in elderly people with type 2 diabetes mellitus, FBG levels are correlated with serum triglyceride and HDL cholesterol levels. Methods: A cross-sectional study of 46 secondary data on elderly patients with diabetes mellitus at Diponegoro National Hospital in Semarang. data analysis using Pearson's correlation test (p<0.05). Results: The Pearson’s correlation test between fasting blood glucose levels and triglyceride levels was p = 0.076, and serum HDL cholesterol was p = 0.270 in elderly patients with type 2 diabetes mellitus. Conclusion: There is no correlation between FBG levels and serum triglyceride and HDL cholesterol levels in elderly people with type 2 diabetes mellitus.